2007
DOI: 10.1177/0047287507302376
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Print Advertising Stimuli in Evoking Elaborate Consumption Visions for Potential Travelers

Abstract: Two imagery-evoking strategies are examined to determine their effectiveness in producing an elaborate consumption vision. Specifically, a 3 × 3 factorial experimental design is employed to examine the effects of pictures and text as advertising stimuli to evoke elaborate consumption visions among the participants within the context of holiday decision making. A MANOVA revealed a main effect for each of the two stimuli. The presence of more concrete pictures contributed to the extent of elaboration and the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(190 citation statements)
references
References 26 publications
(37 reference statements)
5
183
1
1
Order By: Relevance
“…From the perspective of consumer research, a consumer's mental image of a tourism product can be the main source of information available to enhance expectations and facilitate purchasing decisions (Walters, Sparks, & Herington, 2007). When imagery is encouraged through vivid product information, it strongly influences consumers' attitudinal judgments (McGill & Anand, 1989).…”
Section: Mental Imagery Processing and Persuasionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of consumer research, a consumer's mental image of a tourism product can be the main source of information available to enhance expectations and facilitate purchasing decisions (Walters, Sparks, & Herington, 2007). When imagery is encouraged through vivid product information, it strongly influences consumers' attitudinal judgments (McGill & Anand, 1989).…”
Section: Mental Imagery Processing and Persuasionmentioning
confidence: 99%
“…Furthermore, Miller and Stoica (2003) indicated that photographic images of beach scenes effectively stimulated mental imagery processing. More recently, Walters, Sparks and Herington (2007) asserted that the presence of more concrete pictures affects the extent of elaboration and the quality of consumers' consumption visions. Adaval and Wyer (1998) noted that the addition of pictures to a narrative format can encourage readers to imagine the sequence of events, and can facilitate the construction of a representation to be used as a basis for judgment.…”
Section: Processing Pictures and Soundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these fantasies, users develop solid riveting representations of possible consumption activities, imagining themselves utilising a product and anticipating the effects of using it (Goossens, 2000;Jasper and Ouellette, 1994;Petrova and Cialdini, 2005;Walters et al, 2007). This, in turn, facilitates a learning of products and drives actual consumption (Belk et al, 2003;Phillips et al, 1995).…”
Section: A Critical View Of the Imagery Domain And Its Extension To Dmentioning
confidence: 99%
“…Waller et al argue that social telepresence is the necessary condition for the generation of trust in the virtual Interwork environment since trust is usually generated in the social environment [9]. Therefore, the rich sense of immediacy brought by online shopping environment enhances trust among customers; Gefen's research based on e-commerce service scenario reveals that social telepre- …”
Section: The Effect Of the Sense Of Immediacy On The Trustmentioning
confidence: 99%